A Revision of the New World Genera Brachylinga Irwin and Lyneborg and Lysilinga Irwin and Lyneborg (Diptera: Therevidae: Therevinae) with the Description of a New Genus, Elcaribe Webb - Webb, Donald W.; Metz, Mark A. (Zootaxa, 2006)
The species of the New World genera Brachylinga Irwin and Lyneborg, Lysilinga Irwin and Lyneborg, and Elcaribe Webb, gen. nov. are described or redescribed with illustrations of the genitalia and, for most species, a map of its distribution. Keys are provided to identify the species within each genus. Brachylinga includes 24 species, ten of which (Brachylinga albifrons Webb, sp. nov., B. attenuata Webb, sp. nov., B. bicolor Webb, sp. nov., B. concava Webb, sp. nov., B. curacaoensis Webb, sp. nov., B. divaricata Webb, sp. nov., B. laculata Webb, sp. nov., B. mexicana Webb, sp. nov., B. mimica Webb, sp. nov., and B. tridentata Webb, sp. nov.) are new to science. Brachylinga antennata (Kröber) is considered a nomen dubium. Brachylinga interrupta (Kröber) is synonomized under B. chilensis (Macquart) and B. pilosa (Kröber) is synonomized under B. pavida (Coquillett). The genus Lysilinga Irwin and Lyneborg is revised and includes 10 species in North and Central America. Lysilinga chamela Webb, sp. nov., L. crassiseta Webb, sp. nov., L. digita Webb, sp. nov., L. dolichophalla Webb, sp. nov., L. nigra Webb, sp. nov., L. parkeri Webb, sp. nov., and L. recta Webb, sp. nov. are new to science. Lysilinga maculifrons (Kröber) is synonomized under L. pilifrons (Kröber) and L. subrufa (Cole) is synonomized under L. occipitalis (Adams). Elcaribe is described as a new genus and includes 14 species restricted to the Caribbean. Elcaribe anguilla Webb, sp. nov., E. bahamaensis Webb, sp. nov., E. bifidus Webb, sp. nov., E. elongatus Webb, sp. nov., E. glabrus Webb, sp. nov., E. guanaensis Webb, sp. nov., E. longicaudus Webb, sp. nov., E. paniculus Webb, sp. nov., E. scarbroughi Webb, sp. nov., E. starki Webb, sp. nov., and E. stellus Webb, sp. nov. are new to science. Brachylinga abdominalis (Fabricius), B. monensis (Curran), B. obscura (Coquillett), B. laticornis (Loew), and B. squamosa (Hardy) are placed in the genus Elcaribe. Brachylinga monensis (Curran) is synonomized under Elcaribe abdominalis (Fabricius) and B. squamosa (Hardy) is synonomized under Elcaribe obscurus (Coquillett). Psilocephala platycera Loew is determined to be an unjustified new name of Psilocephala laticornis Loew. Brachylinga parvula (Kröber) is placed in the genus Penniverpa (Therevidae), and Brachylinga appendiculata (Macquart) is determined to be a senior subjective synonym of Scepsis nivalis Walker (Tabanidae).